1991
DOI: 10.1111/j.1439-0426.1991.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Size-and weight-dependent cannibalism in hatchery-bred sea bass (Lates calcarifer Bloch)

Abstract: The relationship of predator size to maximum prey size, and predator weight to weight of prey consumed among cannibalistic sea bass (Lates culcurifm Bloch) in a hatchery were assessed. Maximum prey size was computed from morphological measurements (predator mouth width, prey body depth and fish total length), while prey consumption was determined from predators kept in experimental beakers and fed only prey sea bass for a %day period. Maximum prey size was 61-67 % of predator total length (TL,,, = 0.5944 TLpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 12 publications
3
30
0
2
Order By: Relevance
“…The results of predator-prey size ratio agrees with an early studies by Parazo et al (1991) and Qin et al (2004) who found that a barramundi can swallow a sibling with a body length of 70% or less of its own. The present results suggest that sibling cannibalism in juvenile barramundi can begin when body length of a cannibal reaches the body length of about one and half that of the prey fish.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of predator-prey size ratio agrees with an early studies by Parazo et al (1991) and Qin et al (2004) who found that a barramundi can swallow a sibling with a body length of 70% or less of its own. The present results suggest that sibling cannibalism in juvenile barramundi can begin when body length of a cannibal reaches the body length of about one and half that of the prey fish.…”
Section: Discussionsupporting
confidence: 82%
“…Parazo et al (1991) reported that although Weight range [g] the extent of cannibalism in barramundi is size-dependent, the ability of a cannibal to detect conspecifics depends on the habitat complexity and ambient light levels. For visual-feeder fish, searching, chasing, and capturing prey require some degree of light.…”
Section: Discussionmentioning
confidence: 99%
“…El incremento en las diferencias de tallas con el crecimiento en el presente trabajo, característica típica de diversas especies carnívoras (Edwards & Henderson 1987, Dowd & Clarke 1989, Parazo et al 1991, AlvarezLajonchere et al 2002 debe haber contribuido a establecer jerarquías de tallas y con ello el surgimiento del canibalismo. La diferencia de tallas fue mayor al 50%, lo cual rebazó las diferencias reportadas para la especie por Rotman et al (2005) y fueron notablemente superiores a las recomendaciones del 33% para algunas especies carnívoras (Edwards & Henderson 1987, Dowd & Clarke 1989, Parazo et al 1991.…”
Section: Cultivo Larvariounclassified
“…La diferencia de tallas fue mayor al 50%, lo cual rebazó las diferencias reportadas para la especie por Rotman et al (2005) y fueron notablemente superiores a las recomendaciones del 33% para algunas especies carnívoras (Edwards & Henderson 1987, Dowd & Clarke 1989, Parazo et al 1991.…”
Section: Cultivo Larvariounclassified
“…Cannibalism can be a major cause of mortalities and losses during the nursery phase and during the early grow-out (Tattanon and Tiensonggrusmee, 1984, Kungvankij, et al, 1986, NICA, 1986, Parazo, et al, 1991. Sea bass will cannibalize fish up to 61-67% of their own length (Parazo, et al, 1991). To reduce cannibalism graders are used to separate the biggers ones from the small ones (Kungvankij, et al, 1986, Parazo, et al, 1990.…”
Section: Introductionmentioning
confidence: 99%